Exploring the concept of old age in the Italian population: representations and cultural symbolism across different regions - Di Trani, Michela; Cordella, Barbara; Greco, Francesca; Argenti, Elena; Galiccia, Ambra; Gattuso, Maria; Greco, Andrea; Morganti, Francesca (Frontiers in Psychology, 2025)
Global demographic trends show increasing life expectancy, with European countries such as Italy showing a high proportion of older adults. To support healthy aging and design effective health promotion interventions, it is crucial to understand how aging is defined and perceived. This study analyzes representations of aging among individuals in two different Italian cities to determine whether geographical context influences their perspectives. A total of 97 participants aged 55–75 years were interviewed about their experiences of aging, and the interview texts (145,066 tokens) were analyzed using Emotional Text Mining. Aging is perceived as a transitional process involving family responsibilities, changing work roles, and the retirement experience. Common concerns include mental and physical decline, often expressed through comparisons with participants’ past selves or with loved ones. Attitudes toward aging varied: some participants expressed resignation, while others adopted a more proactive approach, often centered around family or social engagement. Geographical and age-based differences were found: respondents from Bergamo were generally more accepting of aging, more focused on health concerns, and more socially active, whereas those from Rome placed greater emphasis on family care. Participants under 65 years of age primarily focused on the transition out of the workforce, while those over 65 years of age focused on the vulnerabilities associated with aging. These findings suggest that tailoring health promotion interventions to individual needs and contextual variables could enhance their effectiveness.